Critical assessment of size exclusion chromatography - Berek, D. (Polimery, 2022)
Size exclusion chromatography (SEC) of synthetic polymers is assessed from the point of view of its both strong and weak points, advantages and drawbacks. Basic information on the SEC retention mechanism arc presented together with the complexity of SEC systems and processes. Present stand of SEC instrumentation is outlined and the role of experimental conditions is described. The need of further development of SEC and of standardization of experimental conditions is demonstrated. The enthalpic interactions, leading to adsorption and enthalpic partition phenomena in the SEC columns are described. It is shown that the latter should be suppressed to obtain reliable SEC results. Alternatively, enthalpic interactions can be deliberately combined with the entropic partition (exclusion) basic SEC retention mechanism either to allow separation of complex polymers exhibiting multiple distributions in their molecular characteristics or to increase selectivity of separation.